2017
DOI: 10.1097/qad.0000000000001646
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B, hepatitis C, and mortality among HIV-positive individuals

Abstract: Objectives:To compare rates of all-cause, liver-related, and AIDS-related mortality among individuals who are HIV-monoinfected with those coinfected with HIV and hepatitis B (HBV) and/or hepatitis C (HCV) viruses.Design:An ongoing observational cohort study collating routinely collected clinical data on HIV-positive individuals attending for care at HIV treatment centres throughout the United Kingdom.Methods:Individuals were included if they had been seen for care from 2004 onwards and had tested for HBV and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 41 publications
5
54
1
1
Order By: Relevance
“…Moreover, in additionally performed Kaplan‐Meier survival analyses, where we compared all patients with and without HCV, we found that HCV‐infected patients had significantly higher probabilities of all‐cause mortality and liver‐related mortality, whereas probabilities for ESLD were the same. Previous studies showed that patients triply infected with HIV, HBV and HCV have significantly higher risk for liver‐related mortality in adjusted models when compared to double infections (HIV/HBV‐, HIV/HCV‐ or HBV/HCV co‐infection) …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, in additionally performed Kaplan‐Meier survival analyses, where we compared all patients with and without HCV, we found that HCV‐infected patients had significantly higher probabilities of all‐cause mortality and liver‐related mortality, whereas probabilities for ESLD were the same. Previous studies showed that patients triply infected with HIV, HBV and HCV have significantly higher risk for liver‐related mortality in adjusted models when compared to double infections (HIV/HBV‐, HIV/HCV‐ or HBV/HCV co‐infection) …”
Section: Discussionmentioning
confidence: 63%
“…In the combined cohorts, those with liver-related mortality were aged older (median 44 [IQR 40-53] vs 37 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] years, P < 0.0001), were more often male (46 [90%] vs 1558 [77%], P = 0.03), and had higher vs 43 , P < 0.0001) at baseline, compared to those without liver-related mortality. Moreover, they had higher incidences of HCV coinfection (8 [ In coinfected subjects, no difference in baseline HIV RNA was observed in those with liver-related mortality vs those with other causes of mortality, while significantly lower baseline CD4 counts (212 [130-420] vs 347 , P = 0.05) were observed in those with liver-related mortality.…”
Section: Frequencies Of Liver Disease and Mortality In The Study Pomentioning
confidence: 99%
“…This suggests that the mortality benefits of SVR in patients with synthetic dysfunction may be slightly lessened and serves as additional leverage for treating patients earlier in their HCV infection, prior to development of more advanced liver disease. From a population standpoint, in addition to the reduction in mortality, treating all patients with HCV regardless of stage of disease would also further reduce HCV transmission …”
Section: Discussionmentioning
confidence: 99%
“…From a population standpoint, in addition to the reduction in mortality, treating all patients with HCV regardless of stage of disease would also further reduce HCV transmission. (18,20,22,28,32) In this cohort, we compared patients who achieved SVR to both untreated patients and patients who were treated but did not achieve SVR, though the comparison between patients who achieved SVR and those who were treated and did not achieve SVR is the more relevant comparison to assess the mortality benefit of SVR with DAA treatment. Unlike many other health care providers and systems, in the VA there were minimal treatment restrictions, all patients were considered for treatment, and extensive outreach occurred to bring patients in for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HCV transmission has been linked to recreational drug use and high‐risk sexual behaviours . Coinfection with HCV and HIV leads to faster progression to advanced liver disease , and there is conflicting evidence as to whether coinfection worsens HIV‐associated outcomes, such as AIDS‐defining events and HIV‐associated mortality .…”
Section: Introductionmentioning
confidence: 99%